Peran Layanan BK dalam Mengatasi Masalah Emosional Anak di Panti Asuhan Muhammadiyah Cingkariang - Rahma Mutia Mutia; M. Arif, Nil Maryani (Pusat Studi Wanita dan Keluarga UGM, 2026)
Children’s emotional development is a crucial aspect of personality formation and social adjustment. Children living in orphanages are more vulnerable to emotional problems due to the loss of parental figures, traumatic experiences, and the demands of adapting to a collective caregiving environment. This study aims to describe the emotional problems experienced by children in orphanages and to examine the role of Guidance and Counseling (GC) services in addressing these problems at Muhammadiyah Cingkariang Orphanage. This research employed a descriptive qualitative approach involving children, caregivers, and counselors as participants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that children experience emotional problems such as anxiety, anger, emotional instability, and social withdrawal. Guidance and Counseling services play a significant role through preventive, developmental, and responsive services, including emotional guidance, individual and group counseling, and expressive therapy. Collaboration between counselors and caregivers enhances the effectiveness of emotional support. This study recommends strengthening sustainable and needs-based Guidance and Counseling services to improve the emotional well-being and psychological resilience of children in orphanage settings. Kata kunci: bimbingan dan konseling, masalah emosional, anak panti asuhan